Hybrid Chains: A Collaboration of Ubiquitin and Ubiquitin-Like Modifiers Introducing Cross-Functionality to the Ubiquitin Code - Pérez Berrocal, David A.; Witting, Katharina F.; Ovaa, Huib; Mulder, Monique P. C. (Frontiers in Chemistry, 2020)
The Ubiquitin CODE constitutes an unique post translational modification language relying on the covalent attachment of Ubiquitin (Ub) to substrates, with Ub serving as the minimum entity to generate a message that is translated into different cellular pathways. The creation of this message is brought about by the dedicated action of writers, erasers, and readers of the Ubiquitin CODE. This CODE is greatly expanded through the generation of polyUb chains of different architectures on substrates thus regulating their fate. Through additional post-translational modification by Ub-like proteins (UbL), hybrid Ub/UbL chains, which either alter the originally encrypted message or encode a completely new one, are formed. Hybrid Ub/UbL chains are generated under both stress or physiological conditions and seem to confer improved specificity and affinity towards their cognate receptors. In such a manner, their formation must play a specific, yet still undefined role in cellular signaling and thus understanding the UbCODE message is crucial. Here, we discuss the evidence for the existence of hybrid Ub/UbL chains in addition to the current understanding of its biology. The modification of Ub by another UbL complicates the deciphering of the spatial and temporal order of events warranting the development of a hybrid chain toolbox. We discuss this unmet need and expand upon the creation of tailored tools adapted from our previously established toolkit for the Ubiquitin Proteasome System to specifically target these hybrid Ub/UbL chains.